The Relationship between Swimming Styles and Il-6 Rs1800795 Polymorphism in Professional Swimmers - Gökhan Tuna, Tolga Polat, Özlem Özge Yilmaz, Sezgin Kapici, Canan Sercan Doğan, Isa Sağiroğlu, Mustafa Savaşan, Niyazi Güven Erdil, Korkut Ulucan (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Athletic performance can be improved with regular training, the contribution of genetic factors, nutrition and psychological factors. The aim of this study is to determine the effect of IL-6 rs1800795 polymorphism in Turkish swimmers and to compare the results with sedentary individuals. Material and Methods: 75 people, including 45 professional swimmers and 30 healthy and sedentary individuals (control), participated in the study. DNA isolation from buccal specimens of athletes was performed using the commercial kit Invitrogen (Van Allen Way, Carlsbad, CA, USA). Genotyping was performed with real-time PCR. Results: GG genotype and G allele were found to be higher in athletes. GG genotype and G allele were found to be higher in the control group. There was no statistically significant difference between the athletes and controls in terms of IL-6 rs1800795 polymorphism. In our study, when the IL-6 rs1800795 gene polymorphism was compared between the groups in terms of swimming styles-distances and genotypes, no significant difference was found. Conclusion: Our study is the first to analyze the IL-6 rs1800795 polymorphism in Turkish swimmers. More studies are needed in terms of IL-6 rs1800795 to reveal the importance of genetic factors in determining the sports performance of the athlete and to clarify their effects on athletic performance. This first report, which includes relevant genetic markers and swimmers, will guide scientists for further studies. Keywords: Genetics, Polymorphisms, Sports Genetics, Single Nucleotide Polymorphism, Swimmers, IL-6